This is How I Can Write: Towards Nepalese English Literature - Karn, Sanjan Kumar (Journal of NELTA, 2013)
Nepalese English is arguably making its presence felt in virtually all domains in Nepal and English literature from Nepal is no exception. The study of creative writings in English by Nepalese literary authors exhibit typical Nepaleseness in such an amplitude that a distinctive English literature can be inferred to be in the making. This paper studies nativization in various genres of literature written in English in Nepal and also contends with the evidences that we have leapt towards Nepalese English literature considered from World Englishes literature perspective. Journal of NELTA, Vol. 17 No. 1-2, December 2012, Page 26-39 DOI: http://dx.doi.org/10.3126/nelta.v17i1-2.8090